Pelatihan Penyemaian Sayuran Akuaponik dan Pembesaran Maggot pada Sistem LETSGO (Lele Terintegrasi Sayuran dan Maggot): Aquaponic Vegetable Seeding and Maggot Rearing Training in the LETSGO System (Integrated Vegetable, Maggot and Catfish) - Mulyawan, Ardi Eko; Heriansah, Heriansah; Yulianto, Harry; Nursyahran, Nursyahran; Aisa, Nur; Fadillah, Fitri Emi; Nurdiana, Nurdiana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This Community Service (PKM) activity was funded by the Directorate General of Research, Technology, and Community Service in the 2024 budget year with contract number 1069/LL9/PK.00.PPM.BATCH.2. This activity took place in Mandalle Village, Pangkep Regency with the title Integrated Farming LETSGO (Integrated Catfish, Vegetables and Maggots) with the partner Turicinnai II Fish Cultivation Group. The problem experienced by the partner was that the pond they had had not been producing for a long time due to the high cost of manufactured feed and the low selling value of catfish. Through the PKM activity carried out by the team from the Balik Diwa Maritime Technology and Business Institute and STIE YPUP Makassar, they succeeded in overcoming the PKM partner's problem by creating 6 (six) complete aquaponic ponds (vegetables and fish), 1 maggot cultivation installation and providing training on maggot cultivation, aquaponic vegetable sowing, and food product sales training. The results of this PKM activity are expected to be able to increase the productivity and profits of PKM partners and increase the benefits of this activity for the surrounding community. The pre-test results showed that the level of knowledge and skills about aquaponics and maggots were generally in the poor category. However, after the learning activities, the post-test results showed that the level of knowledge and skills increased significantly and were generally in the good category. In general, partners considered that aquaponics and maggot maintenance activities were technically easy to apply, economically inexpensive, and ecologically could reduce waste, especially organic waste.